Analisis Biaya Satuan Pelayanan Sectio Caesaria dan Upaya Efisiensinya di RSD Kol. Abundjani Bangko - Tetriadi, Tetriadi; Nurwahyuni, Atik (UI Scholars Hub, 2020)
This study discusses the semester 1 report of 2018 with the difference in income from the caesaria section BPJS service with the hospital rate of Rp 508,932,651. In 2019 UHC (Universal Health Caverage) will be implemented while health BPJS according to Law no. 24 of 2011 was appointed by the government as the health insurance management body. Hospitals need to calculate service costs using unit costs so that they experience devisit. The purpose of this study was to create unit cost services for caesarean sectio cases and their efficiency at RSD Kol. Abundjani Bangko. The research method is a quantitative descriptive study with cross sectional method using double distribution and continued with the calculation of RVU, while service efficiency uses the clinical pathway (CP) hospital plus CP tools from FKM UI. The sample of the study was uncomplicated class 3 sectio caesaria patients, using 2017 retrospective data. The results of the study obtained the service fee for the caesaria section at RSD Kol. Abundjani Bangko, VIP care room Rp.6,704,891, class I Rp.6,491,721, class II Rp.6,320,449 and class III Rp6,503,920 and inefficiency of OK / OKE space Rp571,754, laboratory Rp20,105, medicine Rp203,608, medical equipment and BHP Rp74,084. Conclusion obtained unit cost of sectio caesaria service and its inefficiency at RSD Kol. Abundjani Bangko.